FACTORS AFFECTING GIRLS’ ACADEMIC ACHIEVEMENT: A CASE OF PUBLIC SECONDARY SCHOOLS IN BUKOMBE DISTRICT, GEITA REGION - TANZANIA - T. Rachel, Maphie; M. Mwila, Prospery (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
Some African cultures, customs and traditions have time immemorial hindered girls from attaining quality education similar to their counterparts. Some cultures go further to regard girls and women as second-class citizens and thus are not given opportunities to go beyond basic primary education. In light of this background, this study was conducted to assess factors affecting girls’ academic performance in public secondary schools in Bukombe District. The major objective of this study was to determine the home-, school- and teacher-based factors that affected girls’ academic performance in Form Four National Examinations in public secondary schools. The study was anchored in human capital theory and human needs theory. The study adopted a convergent parallel design under a mixed method approach. Simple random and purposive sampling techniques were used to obtain a sample size of 209 respondents, which included students, teachers and school board members. Questionnaires were used to collect data from students and teachers, while interview schedules were used to collect data from school board members. The reliability of the research instruments was computed through Cronbach’s alpha coefficient, while the content validity was achieved through peer briefing and expert checking. Descriptive analysis with the help of SPSS version 20 was used to analyse quantitative data, while thematic analysis was used to analyse qualitative data. The major findings of the study showed that girls’ academic performance was affected by excessive domestic activities, parental level of education, family size, teenage sexual relationships, distance from home to school, sanitary facilities, teachers’ attitudes and motivation. The study recommended that the identified factors be addressed through social sensitization of the entire community on the importance of educating and empowering the girl child. The study concluded that if the factors affecting girls’ education negatively are dealt with decisively, then girls’ academic performance will improve, thus empowering with equal chance in society.